Edukasi Kesehatan Reproduksi Remaja Putri untuk Meningkatkan Pengetahuan dan Sikap Positif di Era Digital pada Siswi SMA Negeri 1 Kota Dumai - Rahayu, Nova Avianti; Fitria, Sarah (Jurnal Pengabdian UntukMu NegeRI, 2026)
Adolescent girls are a vulnerable group in reproductive health issues, particularly in the digital era where information is widely accessible but not always accurate. Inadequate knowledge and inappropriate attitudes may lead to risky behaviors, reproductive health problems, anemia, and potential stunting in future generations. This study aimed to evaluate the effectiveness of digital-based reproductive health education in improving knowledge and attitudes among female high school students. A community-based educational intervention using a one-group pretest–posttest design was conducted at Senior High School 1 Dumai, Indonesia, involving 100 female students from grades X and XI. The intervention consisted of interactive lectures, group discussions, and digital media utilization.. Knowledge was assessed using structured questionnaires administered before and after the intervention. The proportion of correct answers increased from 68.0% to 89.6%, and the mean score improved from 13.6 to 17.9. Participants demonstrated improved understanding and more positive attitudes toward personal hygiene and healthy behavior. Digital-based reproductive health education effectively improved knowledge and attitudes. Continuous school-based health promotion programs are recommended to support adolescent reproductive health and long-term maternal and child health outcomes.